Transformasi Budaya Baca di MTs Al Ihsan Tanah Grogot Melalui Gerakan Literasi: Studi Kasus dan Implikasinya - Lutfiati, Lutfiati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2024)
This study aims to explore the transformation of reading culture at MTs Al Ihsan Tanah Grogot through the Madrasah Literacy Movement (GLM). The main focus of this research is to analyze the role of teachers and librarians in increasing students' interest in reading as well as the effectiveness of literacy activities implemented. The method used in this research is the phenomenological approach, with data collection through observation, interviews and documentation. The results showed that the active involvement of teachers and librarians in literacy activities contributed significantly to increasing students' interest in reading. In addition, the procurement of relevant and interesting book collections in the library is also an important factor in supporting literacy activities. The conclusion from this study confirms that the success of the literacy program relies heavily on collaboration between all elements of the madrasah and the need to improve the quality and quantity of reading materials. However, the management needs to be improved especially in the aspects of time, variety of books and guidance to students. This research is expected to serve as a reference for other Madrasahs in implementing an effective literacy program.